A vállalat értékét befolyásoló tényezők szerepének vizsgálata angolszász és kontinentális vonatkozásokban - Kiss, Anita (Közép-Európai Közlemények, 2016)
The study examines the value drivers and their influencing role in a regional perspective.The study is based on the theoretical equation emphasizing that the firm’s value is determined by its ability to generate cash flow and the return of the invested capital. However, regarding the firm’s value the management literatureis not uniform. Differences between the Anglo-Saxon and Continental trends can be revealed in areas such as the financial system, the ownership structure of certain countries, the owner controls of various companies and the legal form of the concentration of capital resources. The main objective of this study is to identify the value drivers at a regional level. This study proceeds as follows. The first section presents the shareholder value theory and its practical implementation. The second part describes the stakeholder approach. The third part illustrates the Anglo-Saxon and Continental financial system and value concept. Finally, the fourth section includes concluding remarks.